Factors influencing the individual taxpayers' voluntary compliance - Osman, Mohammad Noor Hisham; Turmin, Siti Zaidah (Human Resource Management Academic Research Society, 2023)
The global issue in the implementation of the Self-Assessment System (STS) is to achieve a satisfactory voluntary tax compliance rate. This motivates this study to investigate the factors that influence voluntary tax compliance among individual taxpayers in Malaysia. Specifically, this study examines the effects of tax knowledge, gender, age, norms, individual values and attitudes, the complexity of the tax system, fairness, tax rates and peer influence on voluntary tax compliance. The study data is gathered from a randomly selected of 101 Kuala Lumpur individual taxpayers. The results of multiple regression analysis show that only (1) gender and (2) norms, values and individual attitudes have a positive relationship with voluntary tax compliance. In conclusion, in Malaysia there is evidence that the rate of voluntary tax compliance depends on personal factors particularly gender and values, not external factors like peers or tax authorities.